(3eSCdI aj JChjd NHQ GdejQGKs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3bGd GdTjN GdeajO QVi Gddg Yfg EPG Sde ddNUhe eG GOYhg ef bhd GdfHi (B"(3U(B" (3fMf eYGTQ GdCfHjGA dGfhQK eG JQcfGg UObg s
(3BNQgG (B:s
(3hMed GdSfI Ydi ehGab GdYehe hGdXGgQ Chdi ef MedgG Ydi eNCdagG hGddg fSCdg GdJhajb hGdgOGjI Edi ShGA GdWQjb s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(998) s
Keywords: (3GdJhMjO hGdedd hGdfMds